Use of land resources for industrial construction (within Malynska UTC) - Pasko, Volodymyr; Maslyak, Petro; Uliganets, Serhii; Shynkarenko, Ulyana (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2025)
The article is devoted to assessing the suitability of land plots within the Malynska TG for the placement of new industrial facilities. Given that the community’s strategic priorities include the development of various industries, the question arises regarding the rational choice of territories: should the community limit itself to using existing production resources, or should it focus on expanding its infrastructure potential? The aim of the study is assessment of the suitability of urban TC land plots for the placement of industrial facilities based on spatial-geographical and socio-economic criteria, taking into account land use restrictions and the potential of the territory for further development. Given the urban nature of the community, it is particularly important to identify promising land plots that meet the criteria for industrial construction. It is envisaged that decisions should be preceded by an analysis of urban planning documentation, environmental and economic indicators. The study applies a methodology of multifactorial assessment of the territory based on geospatial criteria: calculations of proximity to transportation networks (meeting the condition: distance ≤200 m or distance ≥1200 m), settlements (distance ≤1 km or distance ≥11 km), terrain slope (150 ≤ specified slope ≤180), and land use (scored from 0–5 based on land category assessments). The initial data consisted of shape files from OpenStreetMap, providing information on the area's general land use. The calculations revealed that industrial land accounts for nearly 1% (5.71 km2) of the total classified land area.Through the analysis, an additional 12 km2 of prospective land plots were identified, which allow for the expansion of the community’s industrial territorial system. Moreover, the proposed construction sites meet established conditions, do not compromise the quality of life of local residents, minimize environmental changes, and are favorable for potential investors and businesses. It is also worth noting that the community includes 77 rural settlements, some of which are practically uninhabited. This condition serves as an additional factor for further research, particularly if administrative-territorial restructuring shifts from the basic level (territorial community) to the local level (specific settlements). The scientific novelty of this study lies in the comprehensive approach to assessing suitable territories for planned construction. An algorithm was developed that accounted for several factors determining the feasibility of planning activities, thereby reducing project implementation risks. This approach will facilitate future identification and evaluation of specific land plots. The practical significance lies in the fact that the analysis conducted at the level of the selected community, for which «project» territories for industrial use have been established, may be of interest to local authorities and stakeholders. The methodological approach outlined in this research can serve as a «model» for other communities striving to balance economic growth with sustainable land use. By focusing on a thorough examination of land fund distribution, local authorities can create industrial clusters that promote economic synergy, increase employment levels, and improve regional infrastructure.